On the further development of cancer service the Republic of Kazakhstan - Zhandos Burkitbayev; Gulnara Kulkayeva; Adilbek Mukazhanov; Akerke Akadilova; Kuat Oshakbayev (National Scientific Medical Center, 2021)
Introduction. To fight cancer, in 2018, Kazakhstan adopted a comprehensive plan for the development of cancer care for the country's population. Purpose: to present the state of collection of statistics, and perspectives for the oncology service development of the Republic of Kazakhstan through the implementation of the project to create the National Research Oncology Center in Nur-Sultan (NROC). Methods. Official statistical data of international and domestic healthcare organizations, as well as the capabilities of NROC for further development of the oncology service and training of highly professional personnel. Results. The official statistics on cancer morbidity and mortality of the Health Ministry of the Republic of Kazakhstan and KazIOR differs from the WHO (International Agency for Research on Cancer) data. The analysis showed that the current issues of the oncological service of Kazakhstan are low detection rates, insufficient screening coverage of the population, limited access of the population to high-tech methods of diagnosis and treatment, and a shortage of oncologists. To provide the population by oncological service in accordance with international standards, it is planning to: equip the NROC with high-technological medical and diagnostic equipment; functioning of a research center with six scientific laboratories; training of clinical and non-clinical specialists in the world's leading medical and scientific centers. Conclusion. Our study found that in Kazakhstan statistical data on cancer morbidity and mortality are not the same by different officials, and has lower rates of early diagnosis. To become NROC, as center for cancer control in Kazakhstan and in the countries of Central Asia, NROC needs to improve the cancer statistics, innovate a high-quality of cancer care, and provide an accessibility of the population of the Republic of Kazakhstan to high-tech cancer care.